Pengaruh Penggunaan Media Pembelajaran Audio Visual Terhadap Motivasi Belajar Warga Belajar Paket C di Sanggar Kegiatan Belajar Kota Medan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the effect of using audio-visual learning media on the learning motivation of Package C learners at the Medan City Learning Activity Center (SKB). The research problem addressed is the low learning motivation among nonformal learners, which affects their learning outcomes. The purpose of this study is to determine whether the use of Plotagon-based audio-visual media can significantly increase learner motivation. A quantitative approach with a quasi-experimental design (One Group Pretest-Posttest) was used. Data collection was conducted using a Likert-scale questionnaire, validated by an expert and tested on a trial class. The sample consisted of 25 learners. Data analysis included normality tests, homogeneity tests, and hypothesis testing using a paired t-test. The results showed a significant increase in the average motivation score from the pretest (51.84) to the posttest (89.56). The hypothesis test produced a t-count value of 24.156, which was greater than the t-table value of 2.064 at a 5% significance level, with a p-value < 0.001. This indicates a statistically significant difference between the pretest and posttest scores, confirming that the use of Plotagon audio-visual media effectively enhances the learning motivation of Package C learners. The study suggests that integrating interactive and engaging media in nonformal education can improve learning outcomes and student enthusiasm.